Enhancing reading competence through drama-based pedagogy - Balogh, Renáta; Krisztián, Józsa (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2024)
Students' reading comprehension difficulties are a serious challenge that we encounter every day both inside and outside the school environment. Several comprehensive studies (e.g., the Hungarian National Assessment of Basic Competencies – NABC, and the Program for International Student Assessment - PISA) have shed light on that problem and its seriousness. The improvement of reading competence in school is, therefore, a particularly important task. And the methods that improve reading competence play a crucially important role. One such method is drama-based pedagogy. The purpose of this study is to emphasize how the methods of drama-based pedagogy can be used to help the development of reading comprehension. The study highlights that the use of drama-based pedagogy methods strengthens both the motivation and the reading competence. The described drama-based pedagogic methods and games can be used not only within various school lessons but also beyond the classroom setting.
Keywords: reading motivation; reading skills; drama pedagogy